CHEMICAL CONSTITUENTS OF CONES AND LEAVES OF CYPRESS (Cupressus sempervirens L.) GROWN IN TURKEY - Tumen, Ibrahim; Hafizoglu, Harzemsah; Pranovich, Andrey; Reunanen, Markku (Parlar Scientific Publications (P S P), 2010)
Chemical composition of cones, leaves and seeds of Cupressus sempervirens var. pyramidalis Nyman. and Cupressus sempervirens var. horizontalis Mill. were investigated. Hydrodistillaton and SPME (solid phase microextraction) methods were used for the essential oil analysis, besides fatty acids were determined. When comparing C. sempervirens var. pyramidalis with C. sempervirens var. horizontalis, the oil yields of cones were found to be 1.31 ml/100g and 1.59 ml/100g but that of leaves 0.45 ml/100g and 0.82 ml/100g, respectively. The outstanding compounds were alpha-pinene and Delta(3)-carene, found both in leaves and cones by hydrodistillation method. The amounts of alpha-pinene were determined to be 66.8% in var. horizontalis and 52.5% in var. pyramidalis cones, Delta(3)-carene was determined as 13.5% and 19.6%. Likewise, alpha-pinene in leaves was found to be 56.9% and 37.9%, and Delta(3)-carene 13.5% and 25.3%. Generally, alpha-pinene, Delta(3)-carene, beta-myrcene, limonene and alpha-terpinolene were the dominant compounds both in cones and leaves according to SPME method. Lipophilic compounds, such as cupressic acid (horizontalis, 527.1 mg g(-1) and pyramidalis, 412.3 mg g(-1)) and communic acid (horizontalis, 325.7 mg g(-1) and pyramidalis, 317 mg g(-1)) were found in higher quantities on cones than others by hexane extraction. The amounts of cupressic acid or communic acid on seeds of varieties of horizontalis and pyramidalis were found to be 345.4 mg g(-1) and 62.1 mg g(-1), respectively, or 373.6 mg g(-1) and 46.7 mg g(-1).
Keywords: Cypress; Essential Oil; Cupressus Sempervirens; Var. Pyramidalis; Var. Horizontalis; Spme; Hydrodistillation; Lipophilics; Extractives; Cones; Leaves